2017
DOI: 10.1039/c6dt04390a
|View full text |Cite
|
Sign up to set email alerts
|

Multidentate 2-pyridyl-phosphine ligands – towards ligand tuning and chirality

Abstract: In the current work a range of multidentate pyridyl-phosphine ligands are synthesised with tuneable electronic and steric character, through the incorporation of a variety of alcohols into (amino)pyridyl-phosphine frameworks. The stoichiometric reactions of compounds of the type (RN)P(2-py) (2-py = 2-pyridyl) with alkyl as well as aryl alcohols result in the formation of (alkoxy)pyridyl-phosphines (RO)P(2-py) (R = Me, 2-Bu, Ph). This synthetic procedure also allows the introduction of enantiomerically pure alc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 81 publications
0
8
0
Order By: Relevance
“…Our initial interest in 1 – 3 focused on the potential structural/functional effects of the increasing Lewis acidity of the bridgehead as Group 15 is descended. At the top of the group (N and P) the higher electronegativity, combined with the presence of compact lone pairs, is known to lead to ambidentate character in which both the N‐atoms of the 2‐py groups and the Group 15 atom (E) can donate to metal ions (Figure b) . However, the onset of electropositive character and relativistic stabilisation of the lone pair at Bi are anticipated to lead to increasing acceptor character for the bridgehead as the group is descended (Figure b) .…”
Section: Figurementioning
confidence: 99%
“…Our initial interest in 1 – 3 focused on the potential structural/functional effects of the increasing Lewis acidity of the bridgehead as Group 15 is descended. At the top of the group (N and P) the higher electronegativity, combined with the presence of compact lone pairs, is known to lead to ambidentate character in which both the N‐atoms of the 2‐py groups and the Group 15 atom (E) can donate to metal ions (Figure b) . However, the onset of electropositive character and relativistic stabilisation of the lone pair at Bi are anticipated to lead to increasing acceptor character for the bridgehead as the group is descended (Figure b) .…”
Section: Figurementioning
confidence: 99%
“…[29][30][31] This behavior has led to new applications as thermally stable pyridyltransfer reagents as well as reagents for the rapid NMR spectroscopic determination of the enantiomeric excess (ee) of chiral alcohols. [32][33][34] Although the coordination chemistry of tris(2-pyridyl) ligands E(2-py)3 of the lighter Group 15 elements (E = N, P, As) has been extensively studied, [35][36][37][38][39][40][41][42][43][44][45][46][47][48][49] it was only very recently that heavier counterparts containing Sb and Bi have been introduced. Most relevant to the current study, we showed that 6-methyl substitution at the pyridine rings allows the synthesis of the stable ligand [Bi(6-Me-2-py)3] (1) (Fig 1d), which is to date the only example of a tris(2-pyridyl) bismuthine reported.…”
Section: Introductionmentioning
confidence: 99%
“…The 2-pyridyl-phosphine ligands were synthesised according to literature procedures. 35,36 13 C NMR spectra were referenced to TMS, whereas all other heteronuclei were referenced to TMS via the Ξ scale. 59 Unambiguous assignments of the NMR resonances were made on the basis of 2D NMR experiments ( 1 H-1 H COSY and 1 H- 13 C HMBC experiments).…”
Section: Methodsmentioning
confidence: 99%
“…The investigated ligand sets are summarised in Figure 2 and their reactivity and coordination chemistry were recently explored within our group. 35,36 The reaction of tris-2-pyridyl-phosphine P(2-py) 3 (1) with [W(CO) 5 (MeCN)] in a 1 : 1 stoichiometric reaction resulted in the formation of a brown solution. After six days at room temperature 31 P{ 1 H} NMR spectroscopy in CD 3 CN at room temperature revealed full consumption of the free ligand and the presence of various phosphorus-containing tungsten complexes, probably resulting from the various possible coordination modes of the ligand (e.g.…”
Section: Experimental Determination Of the Donor Properties Of 2-pyridyl-phosphines Using W And Mo Carbonyl Complexesmentioning
confidence: 99%